The Effect of Different Physical Treatment and Stimulation Temperature on OSL Decay Curve of Synthetic Quartz Material (International Journal of Innovative Research in Computer Science & Technology, 2022)
Researchers reported, in natural quartz  probability of re-trapping of electrons by shallow TL traps  gets reduced for Optically Stimulated Luminescence (OSL)  at around 160 0C and usual shape of OSL decay curve is  obtained. Under influence of critical physical condition followed by optical stimulation at room temperature in  synthetic quartz material, identical OSL outcomes are  observed. Below these critical physical conditions to the  material neither usual shape of OSL decay curve is obtained nor does it give significant OSL signals. In current investigations, the consequence of different physical  treatment on OSL decay curve of synthetic quartz material is studied. As an OSL outcome, the variations in shape of OSL  decay curve as well as OSL strength over 0 to 100 seconds  of stimulation time are discussed. Changes in OSL outcomes  are responsible to strength of physical treatment to the  sample and stimulation temperature followed by growth of  favourable new centres. The unusual shape of OSL decay  curve suggests the re trapping of optically unconfined electrons still occurred in traps rather than shallow TL traps corresponding to 110oC glow peak. The results are elaborated by resolving components of  complex shapes of OSL decay curve and recorded TL glow  curves before and after OSL for identical physical conditions to the sample.
Keywords: Annealing Treatment; Beta Dose; Elevated Temperature; Optically Stimulated Luminescence (OSL); Synthetic Quartz; Stimulation Temperature